A method for recycling a proton ceramic fuel cell half cell

By synchronously recovering the anode, functional layer and electrolyte of SOFC, the problems of resource waste and environmental pollution in the existing technology are solved, and an efficient and standardized recycling process is achieved, and the theoretical recovery rate can reach 100%.

CN119230860BActive Publication Date: 2025-02-18INNER MONGOLIA UNIV OF TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411747203.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-18
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The lack of efficient and standardized solid oxide fuel cell (SOFC) recycling processes in the prior art leads to waste of resources and environmental pollution.

Method used

A method for recycling a half-cell of a proton ceramic fuel cell is provided, and the synchronous recovery of the anode, functional layer and electrolyte three-layer material through pretreatment, acid corrosion treatment, ball milling and sintering is achieved.

Benefits of technology

It has achieved simplification of the recycling process, reduced energy consumption and environmental friendliness. Theoretically, the recovery rate can reach 100%, and the quality of the recycled half-cell is high and easy to promote.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230860B_ABST
    Figure CN119230860B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of new energy solid oxide fuel cells, and specifically relates to a method for recycling a proton ceramic fuel cell half-cell. Aiming at the technical problem that the traditional battery recycling process is cumbersome and energy-intensive for the recovery of a certain element therein, the present invention provides a method for recycling a SOFC anode, functional layer and electrolyte (collectively referred to as a half-cell), which can achieve the overall recovery of the above three layers of materials, and the recycling process is easy to operate, has low energy consumption, is environmentally friendly, and is easy to promote.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy solid oxide fuel cells, and in particular relates to a method for recovering a proton ceramic fuel cell half cell. Background Art

[0002] Solid oxide fuel cells (SOFCs) are energy conversion devices that use oxide ion conductive ceramic materials as electrolytes. They have high working efficiency and do not require precious metal catalysts, so they are considered to be clean and efficient energy conversion systems. They can use a wide range of fuel gases, including hydrocarbon fuels, coal gas, biomass and other renewable fuels, and have the potential for commercial application. At present, the recycling of solid oxide fuel cells is still very scarce. The waste batteries generated during the research and development and production processes lack efficient and standardized recycling processes, resulting in a certain amount of resource waste; in addition, the current improper battery recycling will cause serious environmental pollution and have a great impact on people's production and life.

[0003] Most of the existing recycling processes are aimed at the recovery of certain elements in solid oxide fuel cells, and there are few reports on the complete recovery process of solid oxide fuel cells. In particular, the recovery of residual materials in the recycling technology of solid oxide fuel cells is still a technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of this, in order to solve the problems existing in the prior art, the present invention provides a method for recycling SOFC anode, functional layer and electrolyte (collectively referred to as half-cell), which can realize the synchronous recovery of three layers of materials: anode, functional layer and electrolyte, and the recycling process is easy to operate, has low energy consumption, is environmentally friendly and easy to promote.

[0005] In order to achieve the above object, the present invention provides a method for recycling a proton ceramic fuel cell half-cell, which adopts the following technical scheme:

[0006] A method for recycling a proton ceramic fuel cell half-cell comprises the following steps:

[0007] (1) Pretreatment of scrapped anode-supported solid oxide fuel cells to obtain recycled half-cell materials;

[0008] (2) The half-cell recovered in step (1) is placed in an agate mortar, crushed and ball-milled into a mixture powder, a 0.5-1.5 mol / L dilute nitric acid solution is prepared, and then 3-5 wt% of the mixture powder is added and washed in the dilute nitric acid solution to obtain anode powder A;

[0009] (3) Add BaCO to the anode powder A obtained in step (2) 3After ball milling and drying, the weight ratio of BaZr 0.3 Ce 0.5 Y 0.1 Yb 0.1 O 3-δ NiO was added in a ratio of 35:65, and ball-milled for a second time to obtain a mixture powder;

[0010] (4) grinding the mixture powder obtained in step (3) and sintering at 1050-1100° C. for 3-5 h to obtain a sintered powder;

[0011] (5) The partially sintered powder obtained in step (4) was ball-milled at 400 rpm for 2 h to obtain a recovered functional layer powder C; starch was added to the partially sintered powder obtained in step (4) at a sintered powder: starch mass ratio of 5:1, and ball-milled at 400 rpm for 0.5 h to obtain a recovered anode powder B.

[0012] It is worth noting that the present invention uses an acid corrosion method to treat the surface of the crystal grains, combined with a molding and sintering method, to achieve material regeneration in order to solve the problems of crystal grain separation and fracture in failed batteries. The results show that the battery has been restored in terms of microstructure, and the battery performance has also reached the level before failure.

[0013] Furthermore, the pretreatment method in step (1) is to manually disassemble the scrapped fuel cell, remove the cathode, and obtain recycled half-cell materials.

[0014] Furthermore, the ball milling method in step (2) is 400 rpm ball milling for 1-2 h, and the raw material of the dilute nitric acid solution is 65.0-68.0 wt% concentrated nitric acid.

[0015] Furthermore, in step (3), BaCO is added 3 The amount is 0.5-1.0 mol% of the Ba content of BZCYYb3511 in the anode powder A obtained in step (2).

[0016] It is worth noting that the present invention improves the microscopic characteristics such as the size and uniformity of the recycled material grains and the macroscopic characteristics such as the sintering activity by adjusting the concentration of dilute nitric acid. 3 To make up for the Ba volatilization loss of the original battery, thereby improving the sintering activity of the material.

[0017] Furthermore, in the step (3), the first ball milling condition is 400 rpm for 1-2 h, and the second ball milling condition is 400 rpm for 2 h.

[0018] Furthermore, the recovery method further comprises:

[0019] (6) According to BaZr 0.3 Ce 0.5 Y 0.1 Yb 0.1 O 3-δ Stoichiometric weighing of BaCO 3 、ZrO 2 、CeO 2 , Y 2 O 3 , Yb 2 O 3 , wherein the molar ratio of each component is: 1: 0.3: 0.5: 0.1: 0.1, ball milling at 400 rpm for 2 h, sintering at 1100 °C for 5 h, and obtaining BZCYYb3511 electrolyte powder D;

[0020] (7) Pressing a half-cell green body: Weigh 0.35-0.4 g of anode powder B, 0.01-0.015 g of recovery functional layer powder C, and 0.01-0.015 g of BZCYYb3511 electrolyte powder D, respectively, and then flatten and press them in a mold in sequence to obtain a pressed half-cell green body;

[0021] (8) Place the pressed half-cell in a high-temperature furnace, cover it with BZCYYb3511 electrolyte powder, and sinter it at 1450-1500℃ for 5 h to obtain a regenerated half-cell.

[0022] Among them, the above-mentioned BaZr 0.3 Ce 0.5 Y 0.1 Yb 0.1 O 3-δ Medium δ<0.1.

[0023] Furthermore, the specific steps of pressing the half-cell green body in step (7) are:

[0024] First, the anode powder B is flattened in a mold with a diameter of 15 mm and pressed into a green body with a pressure of 2 MPa; then the recycled functional layer powder C is flattened and pressed with a pressure of 2 MPa; finally, the BZCYYb3511 electrolyte powder D is flattened and pressed with a pressure of 6 MPa to obtain the pressed half-cell green body.

[0025] Compared with traditional battery recycling processes, the proton ceramic fuel cell half-cell recycling method disclosed in the present invention has fewer steps, simple operation, and low energy consumption. Theoretically, the recovery rate can reach 100%, and the regenerated half-cell assembled with recycled raw materials is of high quality and easy to promote and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0027] Figure 1 The process flow chart of the proton ceramic fuel cell half-cell recovery method of the present invention.

[0028] Figure 2 XRD comparison diagrams of the anode before recovery (bottom), acid-washed powder (middle) and after recovery (top) in Experimental Example 1 of the present invention.

[0029] Figure 3 This is a scanning electron microscope (SEM) morphology image of the anode powder recovered before Experimental Example 1 of the present invention.

[0030] Figure 4 This is the SEM morphology of the acid-washed powder of Experimental Example 1 of the present invention.

[0031] Figure 5 This is the SEM morphology of the anode powder after recovery in Experimental Example 1 of the present invention.

[0032] Figure 6 This is the electrolyte surface morphology of the half-cell before recovery in Experimental Example 2 of the present invention.

[0033] Figure 7 This is the electrolyte surface morphology of the half-cell after recovery in Experimental Example 2 of the present invention.

[0034] Figure 8 This is the cross-sectional morphology of the anode layer of the half-cell before recovery in Experimental Example 2 of the present invention.

[0035] Fig. 9 This is the cross-sectional morphology of the anode layer of the half-cell after recovery in Experimental Example 2 of the present invention.

[0036] Fig.10 This is a cross-sectional SEM image of the half-battery before recovery in Experimental Example 2 of the present invention.

[0037] Fig.11 This is a cross-sectional SEM image of the recovered half-cell in Experimental Example 2 of the present invention.

[0038] Fig.12 It is the power density of the battery before recycling in Experimental Example 2 of the present invention.

[0039] Fig.13 It is the power density of the battery after recycling in Experimental Example 2 of the present invention.

[0040] Fig.14This is a resistance comparison diagram of the recycled batteries in Experimental Example 2 of the present invention. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.

[0043] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.

[0044] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.

[0045] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.

[0046] The present invention discloses a method for recycling a proton ceramic fuel cell half-cell, and belongs to the technical field of new energy solid oxide fuel cells. Aiming at the technical problem that the traditional battery recycling process is complicated and energy-intensive for the recovery of a certain element therein, the present invention provides a method for recycling a SOFC anode, functional layer and electrolyte (collectively referred to as a half-cell), which can realize the overall recovery of the above three layers of materials, and the recycling process is easy to operate, has low energy consumption, is environmentally friendly, and is easy to promote.

[0047] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.

[0048] Example 1

[0049] (1) Collect the used batteries and peel off the cathode of the used batteries, leaving the half-battery materials, namely the anode NiO-BZCYYb3511 and the electrolyte material BZCYYb3511.

[0050] (2) The half-cell materials recovered in step (1) are mixed and ground, and a 0.5 mol / L dilute nitric acid solution is prepared. The ground powder is placed in the dilute nitric acid solution for washing, and then the water is evaporated to dryness to obtain anode powder A.

[0051] (3) First, add BaCO according to 0.5 mol% of the Ba content of BZCYYb3511 in the anode powder A obtained in (2). 3 , ball milled at 400 rpm for 2 h, dried at 90 ℃, and then NiO was added according to the weight ratio of NiO to BZCYYb3511 of 65:35, and the mixed powder was ball milled for a second time at 400 rpm for 2 h.

[0052] (4) Grinding the mixture powder obtained in step (3) and sintering it at 1100°C for 3 h to obtain a sintered powder.

[0053] (5) Starch was added in a weight ratio of 5:1 between the sintered powder and starch, and the mixture was ball-milled at 400 rpm for 2 h to mix the mixture evenly, thereby obtaining a recovered anode powder B.

[0054] (6) According to BaZr 0.3 Ce 0.5 Y 0.1 Yb 0.1 O 3-δ Stoichiometric weighing of BaCO 3 、ZrO 2 、CeO 2 , Y 2 O 3 , Yb 2 O 3 , wherein the molar ratio of each component is: 1: 0.3: 0.5: 0.1: 0.1, ball milling at 400 rpm for 2 h, sintering at 1100 °C for 5 h, and obtaining BZCYYb3511 electrolyte powder D;

[0055] (7) Pressing the half-cell green body: Weigh 0.35 g of anode powder B, 0.01 g of recovery functional layer powder C, and 0.015 g of BZCYYb3511 electrolyte powder D respectively, and then flatten and press them in a mold in sequence to obtain a pressed half-cell green body;

[0056] (8) Place the pressed half-cell in a high-temperature furnace, cover it with BZCYYb3511 electrolyte powder, and sinter it at 1450-1500 °C for 5 h to obtain a regenerated half-cell.

[0057] Example 2

[0058] (1) Collect the used batteries and peel off the cathode of the used batteries, leaving the half-battery materials, namely the anode NiO-BZCYYb3511 and the electrolyte material BZCYYb3511.

[0059] (2) The half-cell materials recovered in step (1) are mixed and ground, and a 1.0 mol / L dilute nitric acid solution is prepared. The ground powder is placed in the dilute nitric acid solution for washing, and then the water is evaporated to dryness to obtain anode powder A.

[0060] (3) First, add BaCO according to 0.5 mol% of the Ba content of BZCYYb3511 in the anode powder A obtained in (2). 3 , ball milled at 400 rpm for 2 h, dried at 90 ℃, and then NiO was added according to the weight ratio of NiO to BZCYYb3511 of 65:35, and ball milled for a second time at 400 rpm for 2 h.

[0061] (4) Grinding the mixture powder obtained in step (3) and sintering it at 1100°C for 3 h to obtain a sintered powder.

[0062] (5) Starch was added in a weight ratio of 5:1 between the sintered powder and starch, and the mixture was ball-milled at 400 rpm for 2 h to mix the mixture evenly, thereby obtaining a recovered anode powder B.

[0063] (6) According to BaZr 0.3 Ce 0.5 Y 0.1 Yb 0.1 O 3-δ Stoichiometric weighing of BaCO 3 、ZrO 2 、CeO 2 , Y 2 O 3 , Yb 2 O 3 , wherein the molar ratio of each component is: 1: 0.3: 0.5: 0.1: 0.1, ball milling at 400 rpm for 2 h, sintering at 1100 °C for 5 h, and obtaining BZCYYb3511 electrolyte powder D;

[0064] (7) Pressing a half-cell green body: Weigh 0.35 g of anode powder B, 0.015 g of recovery functional layer powder C, and 0.015 g of BZCYYb3511 electrolyte powder D respectively, and then flatten and press them in a mold in sequence to obtain a pressed half-cell green body;

[0065] (8) Place the pressed half-cell in a high-temperature furnace, cover it with BZCYYb3511 electrolyte powder, and sinter it at 1450-1500 °C for 5 h to obtain a regenerated half-cell.

[0066] Example 3

[0067] (1) Collect the used batteries and peel off the cathode of the used batteries, leaving the half-battery materials, namely the anode NiO-BZCYYb3511 and the electrolyte material BZCYYb3511.

[0068] (2) The half-cell materials recovered in step (1) are mixed and ground, and a 0.5 mol / L dilute nitric acid solution is prepared. The ground powder is placed in the dilute nitric acid solution for washing, and then the water is evaporated to dryness to obtain anode powder A.

[0069] (3) First, add BaCO according to 1.0 mol% of the Ba content of BZCYYb3511 in the anode powder A obtained in (2). 3 , ball milled at 400 rpm for 2 h, dried at 90 °C, and then NiO was added according to the weight ratio of NiO to BZCYYb3511 of 65:35, and ball milled again at 400 rpm for 2 h.

[0070] (4) Grinding the mixture powder obtained in step (3) and sintering it at 1100°C for 3 h to obtain a sintered powder.

[0071] (5) Starch was added in a weight ratio of 5:1 between the sintered powder and starch, and the mixture was ball-milled at 400 rpm for 2 h to mix the mixture evenly, thereby obtaining a recovered anode powder B.

[0072] (6) According to BaZr 0.3 Ce 0.5 Y 0.1 Yb 0.1 O 3-δ Stoichiometric weighing of BaCO 3 、ZrO 2 、CeO 2 , Y 2 O 3 , Yb 2 O 3, wherein the molar ratio of each component is: 1: 0.3: 0.5: 0.1: 0.1, ball milling at 400 rpm for 2 h, sintering at 1100 °C for 5 h, and obtaining BZCYYb3511 electrolyte powder D;

[0073] (7) Pressing a half-cell green body: Weigh 0.35 g of anode powder B, 0.015 g of recovery functional layer powder C, and 0.015 g of BZCYYb3511 electrolyte powder D respectively, and then flatten and press them in a mold in sequence to obtain a pressed half-cell green body;

[0074] (8) Place the pressed half-cell in a high-temperature furnace, cover it with BZCYYb3511 electrolyte powder, and sinter it at 1450-1500 °C for 5 h to obtain a regenerated half-cell.

[0075] Example 4

[0076] (1) Collect the used batteries and peel off the cathode of the used batteries, leaving the half-battery materials, namely the anode NiO-BZCYYb3511 and the electrolyte material BZCYYb3511.

[0077] (2) The half-cell materials recovered in step (1) are mixed and ground, and a 1.0 mol / L dilute nitric acid solution is prepared. The ground powder is placed in the dilute nitric acid solution for washing, and then the water is evaporated to dryness to obtain anode powder A.

[0078] (3) First, add BaCO according to 1.0 mol% of the Ba content of BZCYYb3511 in the anode powder A obtained in (2). 3 , ball milled at 400 rpm for 2 h, dried at 90 ℃, and then NiO was added according to the weight ratio of NiO to BZCYYb3511 of 65:35, and ball milled at 400 rpm for a second time for 2 h.

[0079] (4) Grinding the mixture powder obtained in step (3) and sintering it at 1100°C for 3 h to obtain a sintered powder.

[0080] (5) Starch was added in a weight ratio of 5:1 between the sintered powder and starch, and the mixture was ball-milled at 400 rpm for 2 h to mix the mixture evenly, thereby obtaining a recovered anode powder B.

[0081] (6) According to BaZr 0.3 Ce 0.5 Y 0.1 Yb 0.1 O 3-δ Stoichiometric weighing of BaCO 3 、ZrO 2 、CeO 2 , Y 2 O3 , Yb 2 O 3 , wherein the molar ratio of each component is: 1: 0.3: 0.5: 0.1: 0.1, ball milling at 400 rpm for 2 h, sintering at 1100 °C for 5 h, and obtaining BZCYYb3511 electrolyte powder D;

[0082] (7) Pressing a half-cell green body: Weigh 0.35 g of anode powder B, 0.015 g of recovery functional layer powder C, and 0.015 g of BZCYYb3511 electrolyte powder D respectively, and then flatten and press them in a mold in sequence to obtain a pressed half-cell green body;

[0083] (8) Place the pressed half-cell in a high-temperature furnace, cover it with BZCYYb3511 electrolyte powder, and sinter it at 1450-1500 °C for 5 h to obtain a regenerated half-cell.

[0084] In order to further demonstrate the beneficial effects of the present invention and to better understand the present invention, the properties and application performance of the proton ceramic fuel cell half-cell recovery method disclosed in the present invention are further illustrated by the following comparative examples and experimental examples, but they should not be construed as limitations on the present invention. The properties of the method obtained by other measurement experiments conducted by technicians in this field based on the above-mentioned invention content and the applications based on the above-mentioned properties are also deemed to fall within the scope of protection of the present invention.

[0085] Experimental Example 1

[0086] The anode powder before recovery, acid-washed powder and recovered anode powder obtained in Example 1 were characterized by XRD. The results are as follows: Figure 2 As shown, it can be seen that the anode components before recycling are NiO and electrolyte BZCYYb3511, and there are no other impurities. In addition to Ni and BZCYYb3511, impurities are also observed in the acid-washed anode, indicating the dissolution of the powder by nitric acid. After recycling, the anode can be seen to have NiO phase and BZCYYb3511 phase, and no other impurities. This shows that the phases of the recycled components are consistent with the components before recycling. SEM observation results ( Figure 3 and Figure 4 ) shows that pickling can significantly reduce the grain size of the anode, which may effectively promote the sintering activity and catalytic activity of the anode. The morphology of the anode after sintering is also different from that of the original anode ( Figure 5 ), which is manifested as more uniform grains. This can effectively improve the sintering activity of the anode.

[0087] Experimental Example 2

[0088] The anode powder recovered from Example 2 was used as a support layer to co-sinter the half-cell obtained by SEM characterization. Figure 7Compared with the half-cell electrolyte before sintering ( Figure 6 ), are basically consistent in terms of electrolyte grain size and morphology, indicating that the present invention successfully obtained the recycled half-cell material. Figure 8 and Fig. 9 These are the SEMs of the half-cell anode before and after recycling. It can be seen that the particles of the recycled anode are more uniform and the grain size is larger. Fig.10 and 11 This is a cross-sectional view of the half-cell before and after recycling. The two are basically the same in morphology.

[0089] The recycled half-cell obtained in Example 2 was used to prepare a recycled full cell. In order to better compare the anodes before and after recycling, the battery cathodes in this example were uniformly made of BaFe 0.75 Co 0.1 Zr 0.1 Nd 0.05 O 3-δ (BFCZN), which is a typical single perovskite structure, is helpful for directional comparative study of the performance of half-cells before and after recycling. Fig.12 and 13 The power density of the whole battery before and after recycling is shown in Figure 2. The maximum power density of the battery before recycling at 700 °C is 1.051.10 W cm -2 The power density after recycling at 700 °C is 1.10 W cm -2 The power density of the recycled battery is slightly improved. From the impedance spectrum ( Fig.14 ), the two are basically at the same level.

[0090] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for recycling a proton ceramic fuel cell half cell, characterized in that: The steps include: (1) Pretreatment of scrapped anode-supported solid oxide fuel cells to obtain recycled half-cell materials; (2) The half-cell recovered in step (1) is placed in an agate mortar, crushed and ball-milled into a mixture powder, a 0.5-1.5 mol / L dilute nitric acid solution is prepared, and then 3-5 wt% of the mixture powder is added and washed in the dilute nitric acid solution to obtain anode powder A; (3) BaCO3 is added to the anode powder A obtained in step (2), and after ball milling and drying, the weight ratio of BaZr 0.3 Ce 0.5 Y 0.1 Yb 0.1 O 3-δ NiO was added in a ratio of 35:65, and ball-milled for a second time to obtain a mixture powder; (4) grinding the mixture powder obtained in step (3) and sintering at 1050-1100° C. for 3-5 h to obtain a sintered powder; (5) The partially sintered powder obtained in step (4) was ball-milled at 400 rpm for 2 h to obtain a recovered functional layer powder C; starch was added to the partially sintered powder obtained in step (4) at a sintered powder: starch mass ratio of 5:1, and ball-milled at 400 rpm for 0.5 h to obtain a recovered anode powder B; (6) According to BaZr 0.3 Ce 0.5 Y 0.1 Yb 0.1 O 3-δ BaCO3, ZrO2, CeO2, Y2O3, and Yb2O3 were weighed in a stoichiometric ratio, wherein the molar ratio of each component was 1: 0.3: 0.5: 0.1: 0.1, ball milled at 400 rpm for 2 h, and sintered at 1100 °C for 5 h to obtain BZCYYb3511 electrolyte powder D; (7) Pressing a half-cell green body: Weigh 0.35-0.4 g of anode powder B, 0.01-0.015 g of recovery functional layer powder C, and 0.01-0.015 g of BZCYYb3511 electrolyte powder D, respectively, and then flatten and press them in a mold in sequence to obtain a pressed half-cell green body; (8) Place the pressed half-cell in a high-temperature furnace, cover it with BZCYYb3511 electrolyte powder, and sinter it at 1450-1500 °C for 5 h to obtain a regenerated half-cell; Among them, the BaZr 0.3 Ce 0.5 Y 0.1 Yb 0.1 O 3-δ Medium δ<0.

1.

2. The recycling method according to claim 1, characterized in that: The pretreatment method in step (1) is to manually disassemble the scrapped fuel cell, remove the cathode, and obtain recycled half-cell materials.

3. The recycling method according to claim 1, characterized in that: The ball milling treatment method in step (2) is ball milling at 400 rpm for 1-2 h, and the raw material of the dilute nitric acid solution is 65.0-68.0 wt% concentrated nitric acid.

4. The recycling method according to claim 1, characterized in that: The amount of BaCO3 added in step (3) is 0.5-1.0 mol% of the Ba content of BZCYYb3511 in the anode powder A obtained in step (2).

5. The recycling method according to claim 4, characterized in that: The conditions for the first ball milling in step (3) are 400 rpm for 1-2 h, and the conditions for the second ball milling are 400 rpm for 2 h.

6. The recycling method according to claim 1, characterized in that: The specific steps of pressing the half-cell green body in step (7) are: First, the anode powder B is flattened in a mold with a diameter of 15 mm and pressed into a green body with a pressure of 2 MPa; then the recycled functional layer powder C is flattened and pressed with a pressure of 2 MPa; finally, the BZCYYb3511 electrolyte powder D is flattened and pressed with a pressure of 6 MPa to obtain the pressed half-cell green body.

Citation Information

Patent Citations

  • Method for preparing sealing pad of solid oxide fuel cell and waste material recovery process

    CN102945974A

  • Method for recovering scandia and zirconia from scandia stable zirconia sintered body

    CN103553128A